2016
DOI: 10.1038/srep28011
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of physical, chemical and biological properties of aridisol from Botswana by the incorporation of torrefied biomass

Abstract: Effective use of agricultural residual biomass may be beneficial for both local and global ecosystems. Recently, biochar has received attention as a soil enhancer, and its effects on plant growth and soil microbiota have been investigated. However, there is little information on how the physical, chemical, and biological properties of soil amended with biochar are affected. In this study, we evaluated the effects of the incorporation of torrefied plant biomass on physical and structural properties, elemental p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 51 publications
1
21
0
Order By: Relevance
“…Furthermore, while the weights of the control pots had returned to their pre-watering levels at four days after water application, the pots that contained soils supplemented with 3%, 5%, and 10% biochar retained 3.3 ± 1.2 g, 16.3 ± 1.2 g, and 42.3 ± 2.1 g more water, respectively. These observations were consistent with those of previous studies [21,55,56] and suggest that the application of jatropha fallen leaf biochar improved the water-holding capacity of the experimental soil. Figure 7.…”
Section: Effects Of Jatropha Fallen Leaf Biochar On Vegetable Growth supporting
confidence: 93%
See 2 more Smart Citations
“…Furthermore, while the weights of the control pots had returned to their pre-watering levels at four days after water application, the pots that contained soils supplemented with 3%, 5%, and 10% biochar retained 3.3 ± 1.2 g, 16.3 ± 1.2 g, and 42.3 ± 2.1 g more water, respectively. These observations were consistent with those of previous studies [21,55,56] and suggest that the application of jatropha fallen leaf biochar improved the water-holding capacity of the experimental soil. Figure 7.…”
Section: Effects Of Jatropha Fallen Leaf Biochar On Vegetable Growth supporting
confidence: 93%
“…Furthermore, the utilization of jatropha wood biochar as an energy source has been described [17]. The effects of jatropha leaf extracts as a herbal ointment [18], mite [Rhipicephalus (Boophilus) annulatus] repellent [19], and therapeutic agent [20] have been studied, and the positive effects of a biochar amendment made from a mixture of jatropha stems and leaves on jatropha seedling growth have been demonstrated [21]. Recently, production of catalytic biocarbons from jatropha biomass has been demonstrated [22,23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Like biochar, torrefied biomass has been predominantly utilized in the coal and energy industry [48] [49]. The recalcitrant torrefied C fraction provides benefits similar to biochar, including enhancing water retention, soil structural stability, soil metabolites, and plant growth promoting microbiota [50].…”
Section: Introductionmentioning
confidence: 99%
“…For example, torrefied poultry litter, produced at 300°C, increased radish ( Raphanus sativa ) yield by direct addition of plant-available nutrients [ 12 ]. Recently, it was demonstrated that fertilization with 3 and 5% PC Jatropha curcas torrefied at 240°C enhanced initial plant growth, nutrient uptake, water retention and structural stability of the soil [ 13 ]. However, torrefied amendments can have high salinity concentrations and have been shown to reduce plant growth, especially at very high application rates (91 Mg ha -1 ) [ 7 ].…”
Section: Introductionmentioning
confidence: 99%